UPAYA KEPALA SEKOLAH MENINGKATKAN KOMPETENSI PEDAGOGIK GURU PADA MASA PANDEMI: SMAN 1 ASEMBAGUS - SAID RIPIN BUKARYO (Mitra Pendidikan, 2022)
The purpose of this study was to determine the efforts made by the principal in improving the pedagogic competence of teachers during the pandemic at SMAN 1 Asembagus. This research is a type of field research with a qualitative approach, which is a study that intends to understand the phenomena experienced by research subjects such as behavior, perception, motivation, action, holistically, and by way of description in the form of words and language, in a special natural context and by utilizing various natural methods (Moleong Lexy J..2017) This research has been carried out at SMAN 1 Asembagus which is located at Jalan Awar-Awar No.999, Awar-awar Village, Asembagus District, Situbondo Regency, and the time for the research is 3 months, starting from February 8, 2021 to April 29, 2021. This research is a teacher of SMAN 1 Asembagus which is 59 teachers In collecting data the researchers used three kinds of techniques, namely: 1) Interview, 2). Observation and 3). Documentation. While the data analysis techniques used in this study are 1). Data Reduction 2) Data Display 3). Conclusion Drawing. Efforts made by school principals in improving pedagogical competence have been maximized, where school principals have provided educational facilities for teachers in the application of online learning processes, involving teachers to participate in various seminars and ICT training activities to improve teacher competence during the teaching and learning process during the pandemic. but there are still obstacles faced in improving pedagogic competence during the pandemic, therefore there are several obstacles faced by teachers during the teaching and learning process during the pandemic such as the difficulty of the internet network, students do not have gadgets, parents who do not understand technology.